Analiza rezerw techniczno-ubezpieczeniowych w zakładach ubezpieczeń majątkowych - Kowalczyk-Lizak, Patrycja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Technical reserves are very important part in management finance in all insurance companies.The one of the basic technical operation in each insurance company is calculating technical reserves on the right level. Technical reserves influence to financial standing, solvency margin and premium rate.The paper presents the selection of ratios characterizing technical reserves of the non-life insurance companies in the Polish market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 270-278